P441 Long-term immunogenicity of vedolizumab in ulcerative colitis and Crohn's disease (GEMINI Programme). (25th January 2019) - Wyant, T; Yang, L; Lirio, R; Rosario, M
Abstract: Background: As previously reported in the pivotal GEMINI 1 (NCT00783718) and 2 (NCT00783692) trials, vedolizumab therapy for ≤ 52 weeks induced low rates of immunogenicity in patients with ulcerative colitis (UC) or Crohn's disease (CD), respectively. [1] [2] We report long-term immunogenicity in patients enrolled in GEMINI 1 (UC) or 2 (CD) followed by the GEMINI long-term safety (LTS) study (NCT00790933/EudraCT 2015-000480-14), including patients on placebo re-treated with vedolizumab in GEMINI LTS. Methods: GEMINI 1 and 2 patients received vedolizumab 300 mg intravenously at Weeks 0 and 2 as induction therapy; Week 6 responders were randomised to vedolizumab every 8 or 4 weeks or placebo for ≤ 52 weeks. All GEMINI 1 or 2 patients were eligible to enrol in GEMINI LTS and receive vedolizumab every 4 weeks until study completion or withdrawal. Blood samples for immunogenicity determination were collected every 16 weeks. Immunogenicity (anti-vedolizumab antibody [AVA] status) was determined using an enzyme-linked immunosorbent assay; AVA-positive samples were characterised using a neutralising assay. Results: Among 1966 patients receiving continuous vedolizumab, 74 (4%) were AVA-positive during GEMINI (11 persistently positive; 42 neutralising AVA-positive). Among 240 patients who received 2 doses of vedolizumab as induction therapy and were randomised to placebo during maintenance in GEMINI 1 or 2 and who were subsequently re-treated with vedolizumab in GEMINI LTS, 42 (18%) were AVA-positive (27 persistently positive; 23 neutralising AVA-positive). Immunogenicity rates were higher during GEMINI 1 and 2 (first 52 weeks of treatment) than GEMINI LTS. Overall, 114 (5%) patients developed an infusion reaction. No patients on continuous vedolizumab with an infusion reaction ( n = 101) were persistently AVA-positive. Two of 13 (15%) patients re-treated with vedolizumab in GEMINI LTS who had an infusion reaction were persistently AVA-positive. Conclusions: Long-term treatment with vedolizumab was associated with low immunogenicity rates consistent with results from GEMINI 1 and 2, even in patients initially treated with vedolizumab induction followed by placebo maintenance in GEMINI 1 and 2 who were subsequently re-treated with vedolizumab in GEMINI LTS. No relationship was observed between immunogenicity and safety. References 1. Feagan BG, Rutgeerts P, Sands BE, et al. Vedolizumab as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2013;369:699–710. 2. Sandborn WJ, Feagan BG, Rutgeerts P, et al. Vedolizumab as induction and maintenance therapy for Crohn's disease. N Engl J Med 2013;369:711–21